WHAT IS THE CAPITAL MARKET REACTION TO THE BOYCOTT ANNOUNCEMENT? - Pertiwi, Dian; Sejati, Fajar Rina (Universitas Pakuan, 2024)
ABSTRACT This study examines the information content of boycott announcements with abnormal returns and trading volume activity as indicators. Companies in the primary consumer goods sector comprise the study population, and 47 samples were obtained after being selected through purposive sampling techniques. Data were tested using a one-sample t-test, a Wilcoxon signed ranked test, and a paired t-test. The results show a negative market reaction around the time of the boycott announcement and a difference in abnormal returns before and after the announcement. However, trading volume activity does not show a significant difference. The implication of this study is to add theoretical evidence to event studies related to testing the information content of boycott announcements. In addition, the study's results can provide insight for investors in interpreting an event such as a boycott action that is responded to as a negative signal. ABSTRAK Penelitian ini menguji kandungan informasi pada pengumuman boikot dengan return taknormal dan aktivitas volume perdagangan sebagai indikator. Perusahaan sektor barang konsumen primer menjadi populasi penelitian dan diperoleh 47 sampel setelah dipilih melalui teknik purposive sampling. Data diuji dengan one sample t-test, wilcoxon signed ranked test, dan paired t-test. Hasil menunjukkan bahwa terdapat reaksi pasar negatif disekitar waktu pengumuman boikot serta terdapat perbedaan return taknormal sebelum dan setelah pengumuman. Namun demikian, aktivitas volume perdagangan tidak menunjukkan perbedaan signifikan. Implikasi penelitian ini adalah menambah pembuktian teori pada studi peristiwa terkait pengujian kandungan informasi pada pengumuman boikot. Selain itu, hasil penelitian dapat menjadi wawasan bagi investor dalam menafsirkan sebuah peristiwa seperti aksi boikot yang direspon sebagai sinyal negatif.